(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2024)
This study aims to examine the relationship between parental social support and the gross motor development of early childhood at PAUD Gideon Wayari. Early childhood is a crucial developmental period often referred to as the "golden age," where optimal stimulation, particularly from the family environment, plays a vital role. Using a quantitative approach, this research involved 15 early childhood participants and applied a questionnaire to assess both parental social support and children’s gross motor skills. Data were analyzed using correlation analysis, revealing a moderate and statistically significant relationship (r = 0.540, p = 0.036) between the two variables. The findings indicate that 29.1% of the variation in children’s gross motor skills is explained by the level of social support provided by their parents. This support includes emotional encouragement, physical engagement, and the provision of an enabling environment for active play. The study supports the theoretical framework of Hurlock and Bronfenbrenner, emphasizing the essential role of family in the physical and psychological development of children. Therefore, the active involvement of parents and teachers in creating safe, supportive, and stimulating environments is crucial for optimizing gross motor development in early childhood.